Cortisol Levels of Shelter Dogs in Animal Assisted Interventions in a Prison: An Exploratory Study - Danila d’Angelo; Serenella d’Ingeo; Francesca Ciani; Michele Visone; Luigi Sacchettino; Luigi Avallone; Angelo Quaranta (Animals, 2021)
Previous studies regarding the Animal Assisted Interventions (AAI) have mainly focused on the beneficial effects of human–animal interactions on human health; whereas the impact of such activities on the welfare of the animals involved has received limited attention. So far, few studies have addressed this issue by evaluating the physiological and behavioral reactions of therapy dogs during the interventions. The aim of this study was to evaluate the potential effect of AAI on the cortisol levels of shelter dogs. Five dogs participated in weekly AAI working activities with adult inmates held at a prison of the South of Italy for two months. Saliva samples were collected every two weeks in three conditions: at the kennel (baseline), after transportation and at the end of the working sessions. The results revealed a significant decrease in the cortisol baseline at the end of the AAI program, suggesting that the activities carried out with humans and in a different environment could improve the welfare of dogs housed in kennels. Moreover, we found that transportation significantly increased subjects’ cortisol levels, suggesting that it is a critical phase that deserves particular care.